Assessment on the Status of post- bloom stages of Rafflesia kerri Meijer in Lojing Highlands, Kelantan, Peninsular Malaysia - Nurulain Mohd Zawawi (2019)
The existence of Rafflesia flower in Kelantan had initiated a lot of association of both non-government and government organization to take a step forward in conserving this unique species. However, no reinforcement had been taken for a while. Rafflesia kerri Meijer contribute into a lot of changes in terms of economic and development especially towards the local community of indigenous people in Lojing Highlands. This changes indicate the importance of conserving this unique plant. An observation on the assessment on the status of Rafflesia kerri Meijer in its post- bloom stages were investigated within the three ha plot in order to find out its population density. The method used is plot less sampling and the observation was conducted at Kg Jedip which the highest point of Rafflesia population. The ecological data were collected based on the observation on site. The elevation and coordinates of all flower (on post- bloom stages) were recorded as raw material for reference. Based on the number of flowers found, the population density of R. kerri flower in post- bloom stages within three ha plot can be estimated. The status of Rafflesia kerri Meijer in Lojing with its mortality rates can be identified. The longevity life cycle of Rafflesia can be guarantee well if its life cycle not disturbed in order to develop a perfect mature fruit seed for next germination. R. kerri life cycle did not end after its blooming phase.